The preparation and properties of 1,1-difluorocyclopropane derivatives - Adekenova, Kymbat S.; Wyatt, Peter B.; Adekenov, Sergazy M. (Beilstein Journal of Organic Chemistry, 2021)
Recently, the functionalization of organic molecules with fluorine substituents has grown rapidly due to its applications in such fields as medicine, agriculture or materials sciences. The aim of this article is to review the importance of 1,1-difluorocyclopropane derivatives in synthesis. It will examine the role of the fluorine substituents in both ring-forming and ring-opening reactions, as well as methods for obtaining difluorocyclopropanes as single enantiomers. Several examples are provided to highlight the biological importance of this class of compounds.
Keywords: biological activity; cyclopropanation; difluorocyclopropane derivatives; synthesis

Fluorine in Bioorganic and Medicinal Chemistry - Itoh, T. (gem-Difluorinated cyclopropanes as key building blocks for novel biologically active molecules, 2009)

(untitled) - Song, X.; Xu, C.; Wang, M. (Tetrahedron Lett., 2017)

Fluorine in pharmaceutical and medicinal chemistry: from biophysical aspects to clinical applications - Welch, J. T. (Applications of pentafluorosulfanyl substitution in life science research, 2012)

(untitled) - Huchet, Q. A.; Kuhn, B.; Wagner, B.; Kratochwil, N. A.; Fischer, H.; Kansy, M.; Zimmerli, D.; Carreira, E. M.; Müller, K. (J. Med. Chem., 2015)

(untitled) - Zhou, Y.; Wang, J.; Gu, Z.; Wang, S.; Zhu, W.; Aceña, J. L.; Soloshonok, V. A.; Izawa, K.; Liu, H. (Chem. Rev., 2016)

(untitled) - Brahms, D. L. S.; Dailey, W. P. (Chem. Rev., 1996)

(untitled) - Dolbier, W. R., Jr; Battiste, M. A. (Chem. Rev., 2003)

(untitled) - Fedoryński, M. (Chem. Rev., 2003)

(untitled) - Atkinson, B. (J. Chem. Soc., 1952)

(untitled) - Tarrant, P.; Lovelace, A. M.; Lilyquist, M. R. (J. Am. Chem. Soc., 1955)

(untitled) - Misani, F.; Speers, L.; Lyon, A. M. (J. Am. Chem. Soc., 1956)

(untitled) - von E. Doering, W.; Hoffmann, A. K. (J. Am. Chem. Soc., 1954)

(untitled) - Tian, F.; Kruger, V.; Bautista, O.; Duan, J.-X.; Li, A.-R.; Dolbier, W. R., Jr; Chen, Q.-Y. (Org. Lett., 2000)

(untitled) - Hine, J.; Langford, P. B. (J. Am. Chem. Soc., 1957)

(untitled) - Hine, J.; Porter, J. J. (J. Am. Chem. Soc., 1957)

(untitled) - Feast, W. J.; Gimeno, M.; Kenwright, A. M. (Macromolecules, 2006)

(untitled) - Volchkov, N. V.; Lipkind, M. B.; Nefedov, O. M. (Russ. Chem. Bull., 2019)

(untitled) - Dolbier, W. R., Jr; Wojtowicz, H.; Burkholder, C. R. (J. Org. Chem., 1990)

(untitled) - Burton, D. J.; Naae, D. G. (J. Am. Chem. Soc., 1973)

(untitled) - Bessard, Y.; Müller, U.; Schlosser, M. (Tetrahedron, 1990)

(untitled) - Bałcerzak, P.; Fedoryński, M.; Jończyk, A. (J. Chem. Soc., Chem. Commun., 1991)

(untitled) - Grudzień, K.; Basak, T.; Barbasiewicz, M.; Wojciechowski, T. M.; Fedoryński, M. (J. Fluorine Chem., 2017)

(untitled) - Birchall, J. M.; Cross, G. E.; Haszeldine, R. N. (Proc. Chem. Soc., London, 1960)

(untitled) - Shibuya, A.; Okada, M.; Nakamura, Y.; Kibashi, M.; Horikawa, H.; Taguchi, T. (Tetrahedron, 1999)

(untitled) - Thomas, M. G.; Suckling, C. J.; Pitt, A. R.; Suckling, K. E. (J. Chem. Soc., Perkin Trans. 1, 1999)

(untitled) - Kubyshkin, V.; Kheylik, Y.; Mykhailiuk, P. K. (J. Fluorine Chem., 2015)

(untitled) - Fujioka, Y.; Amii, H. (Org. Lett., 2008)

(untitled) - Lee, C.-C.; Lin, S.-T.; Ke, S.-Y. (Tetrahedron, 2007)

(untitled) - Oshiro, K.; Morimoto, Y.; Amii, H. (Synthesis, 2010)

(untitled) - Kageshima, Y.; Suzuki, C.; Oshiro, K.; Amii, H. (Synlett, 2015)

(untitled) - Gill, D. M.; McLay, N.; Waring, M. J.; Wilkinson, C. T.; Sweeney, J. B. (Synlett, 2014)

(untitled) - Csuk, R.; Eversmann, L. (Tetrahedron, 1998)

(untitled) - Zheng, J.; Cai, J.; Lin, J.-H.; Guo, Y.; Xiao, J.-C. (Chem. Commun., 2013)

(untitled) - Zheng, J.; Lin, J.-H.; Cai, J.; Xiao, J.-C. (Chem. – Eur. J., 2013)

(untitled) - Dolbier, W. R., Jr; Tian, F.; Duan, J.-X.; Li, A.-R.; Ait-Mohand, S.; Bautista, O.; Buathong, S.; Marshall Baker, J.; Crawford, J.; Anselme, P.; Cai, X. H.; Modzelewska, A.; et al. (J. Fluorine Chem., 2004)

(untitled) - Hang, X.-C.; Gu, W.-P.; Chen, Q.-Y.; Xiao, J.-C. (Tetrahedron, 2009)

(untitled) - Fuchibe, K.; Takayama, R.; Yokoyama, T.; Ichikawa, J. (Chem. – Eur. J., 2017)

(untitled) - Eusterwiemann, S.; Martinez, H.; Dolbier, W. R., Jr (J. Org. Chem., 2012)

(untitled) - Wang, F.; Luo, T.; Hu, J.; Wang, Y.; Krishnan, H. S.; Jog, P. V.; Ganesh, S. K.; Prakash, G. K. S.; Olah, G. A. (Angew. Chem., Int. Ed., 2011)

(untitled) - Rullière, P.; Cyr, P.; Charette, A. B. (Org. Lett., 2016)

(untitled) - Thomson, C. J.; Zhang, Q.; Al-Maharik, N.; Bühl, M.; Cordes, D. B.; Slawin, A. M. Z.; O’Hagan, D. (Chem. Commun., 2018)

(untitled) - Burch, J. D.; Barrett, K.; Chen, Y.; DeVoss, J.; Eigenbrot, C.; Goldsmith, R.; Ismaili, M. H. A.; Lau, K.; Lin, Z.; Ortwine, D. F.; Zarrin, A. A.; McEwan, P. A.; et al. (J. Med. Chem., 2015)

(untitled) - Zhou, J.; Campbell-Conroy, E. L.; Silina, A.; Uy, J.; Pierre, F.; Hurley, D. J.; Hilgraf, N.; Frieman, B. A.; DeNinno, M. P. (J. Org. Chem., 2015)

(untitled) - Hryshchuk, O. V.; Varenyk, A. O.; Yurov, Y.; Kuchkovska, Y. O.; Tymtsunik, A. V.; Grygorenko, O. O. (Eur. J. Org. Chem., 2020)

(untitled) - Fang, Z.; Al-Maharik, N.; Kirsch, P.; Bremer, M.; Slawin, A. M. Z.; O’Hagan, D. (Beilstein J. Org. Chem., 2020)

(untitled) - Bychek, R. M.; Levterov, V. V.; Sadkova, I. V.; Tolmachev, A. A.; Mykhailiuk, P. K. (Chem. – Eur. J., 2018)

(untitled) - Nicolaou, K. C.; Shelke, Y. G.; Dherange, B. D.; Kempema, A.; Lin, B.; Gu, C.; Sandoval, J.; Hammond, M.; Aujay, M.; Gavrilyuk, J. (J. Org. Chem., 2020)

(untitled) - Wang, F.; Zhang, W.; Zhu, J.; Li, H.; Huang, K.-W.; Hu, J. (Chem. Commun., 2011)

(untitled) - Li, L.; Wang, F.; Ni, C.; Hu, J. (Angew. Chem., Int. Ed., 2013)

(untitled) - Brauer, D. J.; Bürger, H.; Buchheim-Spiegel, S.; Pawelke, G. (Eur. J. Inorg. Chem., 1999)

(untitled) - Birchall, J. M.; Haszeldine, R. N.; Roberts, D. W. (J. Chem. Soc., Perkin Trans. 1, 1973)

(untitled) - Mahler, W.; Resnick, P. R. (J. Fluorine Chem., 1974)

(untitled) - Volchkov, N. V.; Lipkind, M. B.; Novikov, M. A.; Nefedov, O. M. (Russ. Chem. Bull., 2015)

(untitled) - Moss, R. A.; Wang, L.; Krogh-Jespersen, K. (J. Am. Chem. Soc., 2009)

(untitled) - Mitsch, R. A. (J. Am. Chem. Soc., 1965)

(untitled) - Seyferth, D.; Hopper, S. P. (J. Org. Chem., 1972)

(untitled) - Nowak, I.; Cannon, J. F.; Robins, M. J. (Org. Lett., 2004)

(untitled) - Tandon, M.; Singh, S.; Xu, L.; Kumar, P.; Wiebe, L. I.; Knaus, E. E.; Gati, W. P.; Tempest, M. L. (Drug Des. Discovery, 1992)

(untitled) - Clark, H. C.; Willis, C. J. (J. Am. Chem. Soc., 1960)

(untitled) - Seyferth, D.; Dertouzos, H.; Suzuki, R.; Mui, J. Y. P. (J. Org. Chem., 1967)

(untitled) - Krause, L. J.; Morrison, J. A. (J. Am. Chem. Soc., 1981)

(untitled) - Eujen, R.; Hoge, B. (J. Organomet. Chem., 1995)

(untitled) - Kirii, N. V.; Pazenok, S. V.; Yagupolskii, Y. L.; Naumann, D.; Turra, W. (Russ. J. Org. Chem., 2001)

(untitled) - Aikawa, K.; Toya, W.; Nakamura, Y.; Mikami, K. (Org. Lett., 2015)

(untitled) - Nakamura, Y.; Fujiu, M.; Murase, T.; Itoh, Y.; Serizawa, H.; Aikawa, K.; Mikami, K. (Beilstein J. Org. Chem., 2013)

(untitled) - Aikawa, K.; Nakamura, Y.; Yokota, Y.; Toya, W.; Mikami, K. (Chem. – Eur. J., 2015)

(untitled) - Tskhovrebov, A. G.; Lingnau, J. B.; Fürstner, A. (Angew. Chem., Int. Ed., 2019)

(untitled) - Taguchi, T.; Okada, M. (J. Fluorine Chem., 2000)

(untitled) - Kagabu, S.; Ando, C.; Ando, J. (J. Chem. Soc., Perkin Trans. 1, 1994)

(untitled) - Lee, C.-C.; Lin, S.-T. (Synthesis, 2000)

(untitled) - Tian, H.; Shimakoshi, H.; Imamura, K.; Shiota, Y.; Yoshizawa, K.; Hisaeda, Y. (Chem. Commun., 2017)

(untitled) - Itoh, T.; Ishida, N.; Ohashi, M.; Asep, R.; Nohira, H. (Chem. Lett., 2003)

(untitled) - Yamani, K.; Pierre, H.; Archambeau, A.; Meyer, C.; Cossy, J. (Angew. Chem., Int. Ed., 2020)

(untitled) - Gassen, K. R.; Baasner, B. (J. Fluorine Chem., 1990)

(untitled) - Taguchi, T.; Kurishita, M.; Shibuya, A.; Aso, K. (Tetrahedron, 1997)

(untitled) - Wang, R.; Ksebati, M. B.; Corbett, T. H.; Kern, E. R.; Drach, J. C.; Zemlicka, J. (J. Med. Chem., 2001)

(untitled) - Wang, M.-X.; Feng, G.-Q.; Zheng, Q.-Y. (Tetrahedron: Asymmetry, 2004)

(untitled) - Yang, Q.; Sheng, M.; Li, X.; Tucker, C.; Vásquez Céspedes, S.; Webb, N. J.; Whiteker, G. T.; Yu, J. (Org. Process Res. Dev., 2020)

(untitled) - Sekine, K.; Ushiyama, A.; Endo, Y.; Mikami, K. (J. Org. Chem., 2020)

(untitled) - Itoh, T.; Mitsukura, K.; Furutani, M. (Chem. Lett., 1998)

(untitled) - Kirihara, M.; Kawasaki, M.; Takuwa, T.; Kakuda, H.; Wakikawa, T.; Takeuchi, Y.; Kirk, K. L. (Tetrahedron: Asymmetry, 2003)

(untitled) - Ferrero, J. C.; De Staricco, E. A. R.; Staricco, E. H. (J. Phys. Chem., 1975)

(untitled) - Jefford, C. W.; Mareda, J.; Gehret, J. C. E.; Kabengele, T.; Graham, W. D.; Burger, U. (J. Am. Chem. Soc., 1976)

(untitled) - Dolbier, W. R., Jr (Acc. Chem. Res., 1981)

(untitled) - Getty, S. J.; Hrovat, D. A.; Xu, J. D.; Barker, S. A.; Borden, W. T. (J. Chem. Soc., Faraday Trans., 1994)

(untitled) - Tian, F.; Lewis, S. B.; Bartberger, M. D.; Dolbier, W. R., Jr; Borden, W. T. (J. Am. Chem. Soc., 1998)

(untitled) - O'Neal, H. E.; Benson, S. W. (J. Phys. Chem., 1968)

(untitled) - Dolbier, W. R., Jr; Sellers, S. F. (J. Am. Chem. Soc., 1982)

(untitled) - Orr, D.; Percy, J. M.; Tuttle, T.; Kennedy, A. R.; Harrison, Z. A. (Chem. – Eur. J., 2014)

(untitled) - Fuchibe, K.; Takayama, R.; Aono, T.; Hu, J.; Hidano, T.; Sasagawa, H.; Fujiwara, M.; Miyazaki, S.; Nadano, R.; Ichikawa, J. (Synthesis, 2018)

(untitled) - Tian, F.; Bartberger, M. D.; Dolbier, W. R., Jr (J. Org. Chem., 1999)

(untitled) - Dolbier, W. R., Jr; Gautriaud, E.; Cai, X. (J. Fluorine Chem., 2005)

(untitled) - Hang, X.-C.; Gu, W.-P.; Chen, Q.-Y.; Xiao, J.-C.; Xu, W.-G.; Liu, S. (J. Fluorine Chem., 2011)

(untitled) - Gajewski, J. J. (J. Am. Chem. Soc., 1970)

(untitled) - Dolbier, W. R., Jr; Sellers, S. F.; Al-Sader, B. H.; Elsheimer, S. (J. Am. Chem. Soc., 1981)

(untitled) - Battiste, M. A.; Tian, F.; Baker, J. M.; Bautista, O.; Villalobos, J.; Dolbier, W. R., Jr (J. Fluorine Chem., 2003)

(untitled) - Kobayashi, Y.; Taguchi, T.; Morikawa, T.; Takase, T.; Takanashi, H. (Tetrahedron Lett., 1980)

(untitled) - Kobayashi, Y.; Taguchi, T.; Morikawa, T.; Takase, T.; Takanashi, H. (J. Org. Chem., 1982)

(untitled) - Xu, W.; Chen, Q.-Y. (Org. Biomol. Chem., 2003)

(untitled) - Sugiishi, T.; Matsumura, C.; Amii, H. (Org. Biomol. Chem., 2020)

(untitled) - Xu, W.; Dolbier, W. R., Jr; Salazar, J. (J. Org. Chem., 2008)

(untitled) - Xu, W.; Ghiviriga, I.; Chen, Q.-Y.; Dolbier, W. R., Jr (J. Fluorine Chem., 2010)

(untitled) - Nihei, T.; Hoshino, T.; Konno, T. (Org. Lett., 2014)

(untitled) - Morikawa, T.; Uejima, M.; Yoda, K.; Taguchi, T. (Chem. Lett., 1990)

(untitled) - Munemori, D.; Narita, K.; Nokami, T.; Itoh, T. (Org. Lett., 2014)

(untitled) - Masuhara, Y.; Tanaka, T.; Takenaka, H.; Hayase, S.; Nokami, T.; Itoh, T. (J. Org. Chem., 2019)

(untitled) - Takenaka, H.; Masuhara, Y.; Narita, K.; Nokami, T.; Itoh, T. (Org. Biomol. Chem., 2018)

(untitled) - Goto, T.; Kawasaki-Takasuka, T.; Yamazaki, T. (J. Org. Chem., 2019)

(untitled) - Specklin, S.; Fenneteau, J.; Subramanian, P.; Cossy, J. (Chem. – Eur. J., 2018)

(untitled) - Hang, X.-C.; Chen, Q.-Y.; Xiao, J.-C. (J. Org. Chem., 2008)

(untitled) - Hang, X.-C.; Chen, Q.-Y.; Xiao, J.-C. (J. Org. Chem., 2011)

(untitled) - Cheng, Z.-L.; Xiao, J.-C.; Liu, C.; Chen, Q.-Y. (Eur. J. Org. Chem., 2006)

(untitled) - Yang, T.-P.; Lin, J.-H.; Chen, Q.-Y.; Xiao, J.-C. (Chem. Commun., 2013)

(untitled) - Yang, T.-P.; Li, Q.; Lin, J.-H.; Xiao, J.-C. (Chem. Commun., 2014)

(untitled) - Dolbier, W. R., Jr; Cornett, E.; Martinez, H.; Xu, W. (J. Org. Chem., 2011)

(untitled) - Isogai, K.; Nishizawa, N.; Saito, T.; Sakai, J.-i. (Bull. Chem. Soc. Jpn., 1983)

(untitled) - Wenz, J.; Rettenmeier, C. A.; Wadepohl, H.; Gade, L. H. (Chem. Commun., 2016)

(untitled) - Song, X.; Xu, C.; Du, D.; Zhao, Z.; Zhu, D.; Wang, M. (Org. Lett., 2017)

(untitled) - Xu, J.; Ahmed, E.-A.; Xiao, B.; Lu, Q.-Q.; Wang, Y.-L.; Yu, C.-G.; Fu, Y. (Angew. Chem., Int. Ed., 2015)

(untitled) - Ahmed, E.-A. M. A.; Suliman, A. M. Y.; Gong, T.-J.; Fu, Y. (Org. Lett., 2019)

(untitled) - Ahmed, E.-A. M. A.; Suliman, A. M. Y.; Gong, T.-J.; Fu, Y. (Org. Lett., 2020)

(untitled) - Ni, J.; Nishonov, B.; Pardaev, A.; Zhang, A. (J. Org. Chem., 2019)

(untitled) - Barnett, C. J.; Huff, B.; Kobierski, M. E.; Letourneau, M.; Wilson, T. M. (J. Org. Chem., 2004)

(untitled) - Fensome, A.; Ambler, C. M.; Arnold, E.; Banker, M. E.; Brown, M. F.; Chrencik, J.; Clark, J. D.; Dowty, M. E.; Efremov, I. V.; Flick, A.; Gerstenberger, B. S.; Gopalsamy, A.; et al. (J. Med. Chem., 2018)

(untitled) - Forman, S. B.; Pariser, D. M.; Poulin, Y.; Vincent, M. S.; Gilbert, S. A.; Kieras, E. M.; Qiu, R.; Yu, D.; Papacharalambous, J.; Tehlirian, C.; Peeva, E. (J. Invest. Dermatol., 2020)

(untitled) - Ninomiya, K.; Tanimoto, K.; Ishida, N.; Horii, D.; Sisido, M.; Itoh, T. (J. Fluorine Chem., 2006)

(untitled) - Collado, I.; Pedregal, C.; Bueno, A. B.; Marcos, A.; González, R.; Blanco-Urgoiti, J.; Pérez-Castells, J.; Schoepp, D. D.; Wright, R. A.; Johnson, B. G.; Kingston, A. E.; Moher, E. D.; et al. (J. Med. Chem., 2004)

WO Patent - Buettelmann, B.; Kocer, B.; Kuhn, B.; Prunotto, M.; Richter, H.; Ritter, M.; Rudolph, M.; Satz, A. L. (Triaza-spirodecanones as DDR1 inhibitors, 2017)

WO Pat. Appl. - Lim, J.; Kelley, E. H.; Methot, J. L.; Zhou, H.; Petrocchi, A.; Mansoor, U. F.; Fischer, C.; O'Boyle, B. M.; Guerin, D. J.; Bienstock, C. E.; Boyce, C. W.; Daniels, M. H.; et al. (Novel compounds that are ERK inhibitors, 2013)

WO Pat Appl. - Marcin, L. R.; Higgins, M. A.; Bronson, J. J.; Zusi, F. C.; Macor, J. E.; Ding, M. (Triazolopyrimidine ether derivatives and their use in neurological and psychiatric disorders, 2015)

WO Pat. Appl. - Dilger, A. K.; Corte, J. R.; De Lucca, I.; Fang, T.; Yang, W.; Wang, Y.; Pabbisetty, K. B.; Ewing, W. R.; Zhu, Y.; Wexler, R. R.; Pinto, D. J. P.; Orwat, M. J.; et al. (Macrocyclic factor XIA inhibitors condensed with heterocycles, 2015)

(untitled) - Liu, C.-H.; Wang, S.-A.; Ruszczycky, M. W.; Chen, H.; Li, K.; Murakami, K.; Liu, H.-w. (Org. Lett., 2015)

USSR Patent - Franke, H.; Joppien, H.; Franke, H. (Method of producing derivatives of difluorocyclopropane, 1989)